Missing knowledge of gendered power relations among non-governmental organisations doing right to health work: a case study from South Africa - Mayara Fontes Marx; Leslie London; Alex Müller (BMC, 2018)
Abstract Background Despite 20 years of democracy, South Africa still suffers from profound health inequalities. Gender roles and norms are associated with individuals' vulnerability that lead to ill-health. For instance, gender inequality influences women's access to health care and women's agency to make health-related decisions. This paper explores gender-awareness and inclusivity in organisations that advocate for the right to health in South Africa, and analyses how this knowledge impacts their work? Methods In total, 10 in-depth interviews were conducted with members of The Learning Network for Health and Human Rights (LN), a network of universities and Civil Society Organisations (CSOs) which is explicitly committed to advancing the right to health, but not explicitly gendered in its orientation. Results The results show that there is a discrepancy in knowledge around gender and gendered power relations between LN members. This discrepancy in understanding gendered power relations suggests that gender is 'rendered invisible' within the LN, which impacts the way the LN advocates for the right to health. Conclusions Even organizations that work on health rights of women might be unaware of the possibility of gender invisibility within their organisational structures.